Marketing and Regulatory Issues for Functional Foods and Nutraceuticals - Rehan Haider; Geetha Das (International Journal of Economics, Business Management and Accounting (IJEBMA), 2021)
Functional foods and nutraceuticals have gained substantial attention in recent years due to their potential to offer health benefits beyond basic nutrition. These products bridge the gap between food and pharmaceuticals, offering an appealing solution for health-conscious consumers. However, the marketing of functional foods and nutraceuticals is not without its challenges. One primary concern is regulatory compliance. These products often straddle the line between food and medicine, making it crucial to navigate complex regulatory requirements. Marketing claims, such as "heart-healthy" or "immunity-boosting," need to be substantiated by scientific evidence, and companies must ensure compliance with regional food and drug regulations to avoid legal repercussions. Consumer skepticism is another issue. Although functional foods and nutraceuticals are designed to improve health, consumers remain cautious about their effectiveness and safety. Overcoming this skepticism necessitates transparent and credible communication, backed by well-designed clinical studies and endorsements from healthcare professionals. Competitive differentiation is a constant challenge. The market is flooded with similar products, making it challenging to stand out. Companies must invest in branding, innovative product development, and unique marketing strategies to distinguish themselves from the competition. Price sensitivity is a critical factor. Functional foods and nutraceuticals tend to be more expensive than regular foods, which can deter price-conscious consumers. Marketing should focus on the long-term health benefits and value proposition to justify the premium pricing. Distribution and accessibility can be problematic. Functional foods and nutraceuticals are not always readily available in all regions, limiting market reach. Expansion strategies and partnerships with retailers are crucial to ensuring widespread accessibility. Educating both consumers and healthcare professionals is essential